Internal Structure and Consistency of the Spanish Version of the Six-Item Female Sexual Function Index (2019)
Objective: The purpose of this paper is to evaluate the structure of the Spanish version of the FSFI-6 in climacteric Colombian women. Methods: The validation study involved 1,427 sexually active women aged between 40 and 59 years. Cronbach’s alpha, McDonald’s omega and confirmatory factor analysis were calculated. Results: The Cronbach’s alpha was 0.876 and the McDonald’s omega was 0.886. The one- dimension model did not fit, chi-square=582.04, df=9, p<0.001, RMSEA=0.211 (90%CI 0.197-0.226), CFI=0.888 and TLI=0.813. Conclusion: The FSFI-6 presents a one-dimensional structure with high internal consistency in climacteric women from the Caribbean coast of Colombia. But, the data’s goodness of fit is inadequate. These findings need to be verified in other populations.